Pengembangan Media Pembelajaran Berbasis Aplikasi Educaplay pada Pembelajaran Pendidikan Pancasila di Kelas V Sekolah Dasar - Fitri, Nurul; Rahmatina, Rahmatina (TSAQOFAH, 2025)
The limited use of technology-based learning media in elementary schools, particularly in Grade V Pendidikan Pancasila instruction, has negatively impacted students' focus and comprehension of the material. This study aims to develop an instructional medium using the Educaplay application, employing the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research method involved needs analysis, curriculum and content analysis, media design, validation by subject matter, language, and media experts, and implementation across three elementary schools (SDN 16, 26, and 28 Air Tawar Timur). The practicality of the media was assessed through teacher and student response questionnaires, while effectiveness was measured using N-Gain analysis from pretest and posttest results. Validation results indicated a very high level of validity—96% from content experts, 98% from language experts, and 90% from media experts. Practicality testing yielded average scores above 89%, indicating the media is highly practical. Effectiveness testing showed a significant improvement in learning outcomes, with N-Gain scores in the high category (88.88%–95.65%). These findings indicate that the Educaplay-based instructional media is valid, practical, and effective in enhancing the quality of Pendidikan Pancasila learning in Grade V elementary classrooms.